Genital chlamydia prevalence in Europe and non-European high income countries: systematic review and meta-analysis. - Shelagh M Redmond; Karin Alexander-Kisslig; Sarah C Woodhall; Ingrid V F van den Broek; Jan van Bergen; Helen Ward; Anneli Uusküla; Björn Herrmann; Berit Andersen; Hannelore M Götz; Otilia Sfetcu; Nicola Low (PLoS ONE, 2015)
Background Accurate information about the prevalence of Chlamydia trachomatis is needed to assess national prevention and control measures. Methods We systematically reviewed population-based cross-sectional studies that estimated chlamydia prevalence in European Union/European Economic Area (EU/EEA) Member States and non-European high income countries from January 1990 to August 2012. We examined results in forest plots, explored heterogeneity using the I² statistic, and conducted random effects meta-analysis if appropriate. Meta-regression was used to examine the relationship between study characteristics and chlamydia prevalence estimates. Results We included 25 population-based studies from 11 EU/EEA countries and 14 studies from five other high income countries. Four EU/EEA Member States reported on nationally representative surveys of sexually experienced adults aged 18-26 years (response rates 52-71%). In women, chlamydia point prevalence estimates ranged from 3.0-5.3%; the pooled average of these estimates was 3.6% (95% CI 2.4, 4.8, I² 0%). In men, estimates ranged from 2.4-7.3% (pooled average 3.5%; 95% CI 1.9, 5.2, I² 27%). Estimates in EU/EEA Member States were statistically consistent with those in other high income countries (I² 0% for women, 6% for men). There was statistical evidence of an association between survey response rate and estimated chlamydia prevalence; estimates were higher in surveys with lower response rates, (p = 0.003 in women, 0.018 in men). Conclusions Population-based surveys that estimate chlamydia prevalence are at risk of participation bias owing to low response rates. Estimates obtained in nationally representative samples of the general population of EU/EEA Member States are similar to estimates from other high income countries.